Genotyping of Exon 2 BRCA1for Breast Cancer in Iraqi Women by Sanger Sequencing - MahanaOied Hussein1 , Khitam Abdul-Wahhab Ali2 , Najwa S. Ahmed3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Sporadic, familial and hereditary kinds account for approximately (70-75%), (10-15%) and(five-10%) of all breast cancers respectively. Although numerous chance factors predispose to hereditarybreast cancer, the maximum mighty is mutations within the breast cancer susceptibility genes, BRCA1.Animportant example for tumor suppressor genes are BRCA1 .Material and methods:We examined the frequency of the BRCA1 Exon 2 in 80Iraqi breast cancer (BC)patients, and 60 controls and then the previously genotyped variants in ages between 25 to 45 and also 45 to70,who attended the Oncology Hospital in the City of Medicine during the period from June 2018 to April2019, The products of PCR from amplification of BRCA gene analyzed by PCR-sequencing method.Result: Our study refer to the genotyping of BRCA1 that distributed to ( GG and TT genotyping while TGequal zero.). A significant change was observed in the comparison between the newly diagnosis group andthe control group. T allele was associated with 3.0 fold higher risk for cancer than the G allele (OR=2.38;p=0.041). In BRCA-1 Polymorphism, the odd ratio for the mutant GG genotype was 2.12 with p=0.0141indicating that Patients with an allele GG genotype a higher risk factor of newly diagnosis group comparedto patients who carry allele TT genotype and control group. Also BRCA have a positive correlation with ageand BMI in newly and treatment group also with some biomarkers.Conclusion:SNP variants and different genotypes of BRCA1 have important roles in the development ofcancer. Their application on such patients would discriminate those with high susceptibility to DNA damagefrom those with low susceptibility. This is specially applied for the GG and TT variants of BRAC1 Exon 2.